(untitled) (Journal of Medical & Health Sciences Review, 2025)
Foot pain is a common yet under-recognized issue among workers in physically demanding occupations, particularly in the garment industry. Tailors, due to prolonged sitting, repetitive movements, and poor ergonomic conditions, are at high risk for developing musculoskeletal disorders, including foot pain. This study aimed to assess the effects of foot pain due to repetitive movements of foot on work related quality of life in tailors. An observational cross-sectional study was carried out over a span of 6 months to find out the effects of foot pain due to repetitive movements of foot on work related quality of life in tailors in which 184 tailors aged between 25–60 years were taken as a sample by using non-probability convenient sampling technique. Data were collected using the Foot Function Index (FFI) and Work-Related Quality of Life Scale and analyzed through SPSS version 25 by applying Correlation Analysis. The findings revealed a moderate negative correlation between foot pain and WRQoL (r = –0.367, p < 0.001), indicating that higher levels of foot discomfort were associated with reduced work-related well-being. These results highlight the need for preventive strategies such as ergonomic modifications and foot care awareness in physically intensive occupations like tailoring.